(untitled) (Sebha University Conference Proceedings, 2024)
Drought and salinity are two of the foremost environmental stresses which affecting seriously plant growth and productivity worldwide. these stresses limited water supply results in disturbance of osmotic balance, impaired metabolic activity at cellular level and excessive reactive oxygen species (ROS). The influences of different levels of salinity and drought applied on pepper plant during germination and seedling development stages. Exposure of Capsicum annum L. during germination period to different levels of drought increased in germination parameters (germination percentages, mean germination time…...et), whereas sea water concentrations were decreased these parameters. In addition, all investigated traits of chili seedling were impaired by higher levels water stress. Irrigated after 6 days had highest average values of almost seedling measurements. the higher concentrations (50 and 70%) of sea water were greatly inhibited of seedling development. The response patterns of chili plants to different environmental stresses used in this study were varied with different growth stages. Where, sea water had strong effects on chili plant at seed germinated and seedling development periods, whereas water stress had more response at seedling development stages.